Influence of nitrogen, Azospirillum sp and farm yard manure on the yield, rhizome rot and quality of ginger (Zingiber officinale Rosc.) - B K Sahoo, D K Dash, NC Mishra, (Journal of Spices and Aromatic Crops, 2008)
The influence of Nitrogen fertilizer, Azosprillium sp. farm yard manure and their combinationson ginger (Zingiber officinale Rosc) was studied at Pottangi (Orissa). The highest fresh rhizomeyield (18.70 q/ha), lowest rhizome rot (11%) and quality ginger (5.82% oleoresin content)with B: C ratio of 2:4 could be obtained in recommended dose of fertilizers 100% combinedwith Azospirillum sp. 10Kg/ha and FYM 10t/ha. Azospirillum has a prominent role in increasingproductivity and quality of ginger while reducing the most challenging disease i.e the Rhizomerot of ginger. In some situations, inorganic N level can be reduced to 30% level in presence ofbio-fertilizers to obtain economic return. In all organic farming situations, addition orAzospirillum to package of practices will enhance the production of ginger.